Tricuspid insufficiency: echocardiographic techniques to evaluate a forgotten valve disease (2019)
The tricuspid valve is traditionally known as the forgotten valve, due to its importance given in the published literature and in the clinical trials available over the years. Echocardiography, with its different imaging modes, remains the reference standard for determining the mechanism and severity of the tricuspid insufficiency. In the past few years, research has enabled the 3-dimensional technique to be introduced, both in the transthoracic and trans-oesophageal examination. This permits the tricuspid valve anatomy to be evaluated from its atrial or ventricular aspect, as well as to analyse the structure of its valves, its anatomical variations. Furthermore, the different mechanisms or lesions that can affect its proper functioning and lead to tricuspid regurgitation, as well as the subsequent morbidity and mortality that may arise, can also be examined. © 2018 Sociedad Colombiana de Cardiología y Cirugía Cardiovascular